Bilingualism and the Development of Executive Function: The Role of Attention - and Bialystok, Ellen (Child development perspectives, 2015)
This paper reviews research examining the effect of bilingualism on children’s cognitive development, and in particular, executive function. Studies reporting bilingual advantages in various tasks are described with the purpose of identifying the process or executive function component that might be responsible for this bilingual advantage. Several possibilities are discussed, such as inhibitory control. Finally, the role of attention is proposed as a fundamental process that initiates developmental differences in bilingual children from as early as infancy.